The Intellectual Legacy of Islam: The Evolution of Educational Institutions from the Classical to the Medieval Period - Ikbal, Muhammad; Ismail, Fajri; Zuhdiyah, Zuhdiyah; Sukardi, Ismail (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic education in Indonesia has deep and unique roots, evolving from the assimilation of Islamic values with local culture since the 13th century through institutions such as pesantren and surau, which served as centers of knowledge and moral guidance for society. This study employs a qualitative research method. The findings indicate that the transformation of Islamic educational institutions from informal systems to formal institutions marks a significant development in the history of Islamic education. Madrasahs emerged as structured centers of learning with more established curricula and teaching systems, while simultaneously facing challenges such as conservatism and limited accessibility. On the other hand, the epistemological dynamics of Islamic education demonstrate a synthesis between revelation and reason, forming a holistic foundation of knowledge. This was reflected in the golden age of rapid scientific advancement during the classical period, followed by an emphasis on normative sciences during the medieval period, all while preserving intellectual traditions through sanad systems and rigorous learning methodologies. The intellectual contributions of Islam not only enriched the Islamic world but also had a global impact through the transmission of knowledge to Europe. Despite socio-political challenges, the value of balance between revelation and reason remains a vital legacy for the development of adaptive and relevant Islamic education to this day.